Communication in Multiperiod Agencies with Production and Financial Decisions* - CHRISTENSEN, PETER OVE; FELTHAM, GERALD A. (Contemporary Accounting Research, 1993)
This paper examines a two‐consumption date principal/agent model in which the manager receives private information at the first date. After observing his private information, the manager (agent) selects both the capital and personal effort he will invest in production. Operating cash flows are realized at both dates and any uninvested funds at the initial date are either paid out as a dividend to the equityholders (principal) or invested in zero net present value investments that require no effort. The aggregate cash flow at the second date is paid out as a dividend to the equityholders. The compensation contract specifies the manager's compensation as a function of the information available at the two dates. The key issue is whether it is valuable to have the contract based on the agent's communication of his private information. As in a single‐consumption date model, communication may permit the implementation of more efficient incentives with respect to the manager's action choices. In addition, communication can facilitate the smoothing of the manager's consumption over the two dates. Direct communication can have positive value, but the analysis identifies a number of factors that can result in communication having no value. These factors include no direct preference for effort, public reporting of the private information at the second date, access to personal investments, and access to a dividend policy that will costlessly convey the private information through first‐date dividends. Although access to personal investments may make communication redundant (since it is an alternative means of smoothing consumption), the analysis identifies conditions under which the equityholders would prefer to use communication and restrict the manager's access to personal investments (since it can have a negative effect on incentives). Résumé. Les auteurs examinent un modèle mandant‐mandataire à deux dates de consommation dans lequel le gestionnaire reçoit de l'information privilégiée à la première des deux dates. Après avoir observé l'information privilégiée, le gestionnaire (c'est‐à‐dire le mandataire) sélectionne le capital et l'effort personnel qu'il investira dans la production. Les flux monétaires provenant de l'exploitation sont réalisés aux deux dates, et tous les fonds qui ne sont pas investis à la date initiale sont soit versés sous forme de dividendes aus. actionnaires (c'est‐à‐dire les mandants), soit investis dans des placements à valeur actualisée nette nulle et qui n'exigent aucun effort. Les flux monétaires totaux à la seconde date sont versés sous forme de dividendes aux actionnaires. Selon le contrat de rémunération, la rétribution des gestionnaires est fonction de l'information disponible aux deux dates. Le principal problème consiste à déterminer si le fait de baser le contrat sur la communication par le mandataire de l'information privilégiée dont il dispose présente un intérêt. Comme dans un modèle à une seule date de consommation, la communication peut permettre la mise en place de stimulants plus efficients en ce qui a trait au choix du gestionnaire concernant son plan d'action. En outre, la communication peut faciliter le nivellement de la consommation du gestionnaire entre les deux dates. La communication directe peut avoir une valeur positive, mais l'analyse permet de cerner plusieurs facteurs qui peuvent retirer toute valeur à une communication. Au nombre de ces facteurs figurent: l'absence de préférence directe pour l'effort, la communication publique de l'information privilégiée à la seconde date, l'accès aux placements personnels et l'accès à une politique de dividendes qui livrera sans frais l'information privilégiée par le truchement du versement de dividendes de la première date. Bien que l'accès aux placement personnels puisse rendre la communication redondante (puisqu'il s'agit d'un moyen de rechange de niveler la consommation), les auteurs définissent les conditions dans lesquelles les actionnaires préféreraient utiliser la communication et restreindre l'accès du gestionnaire aux placements personnels (puisqu'ils peuvent avoir un effet négatif sur les stimulants).